Fe-Mn/ZrO2 catalysts: Sulfate-based-advanced oxidation process for the degradation of olive oil industry model pollutants - Camila M. Loffredo; Mariana Dennehy; Mariana Alvarez (Catalysis Communications, 2023)
Fe, Mn and a bimetallic FeMn catalysts supported on ZrO2 were synthesized and tested for the activation of persulfate (PS) and peroxymonosulfate (PMS) in the degradation reaction of three different organic compounds: cinnamic acid (CA), benzoic acid (BA), and catechol (C). The catalysts were prepared and tested in order to evaluate the effect of the metal and the metal combination on the generation of reactive oxygen species (ROS). The characterization of the catalysts was carried out by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and atomic absorption spectroscopy (AAS).The best degradation results were obtained when PMS was activated with the bimetallic Fe-Mn/ZrO2 catalyst in the CA degradation. Moreover, the Fe-Mn/ZrO2 catalyst reusability was tested for up to three consecutive cycles of reaction, with mineralization levels >90%.A synergistic effect between the Fe and Mn metal species, which increases the catalyst activity if compared to the monometallic catalysts, is postulated. Both sulfate and hydroxyl radicals were generated in the PMS activation process. The activation mechanisms of the oxidants were proposed.